Manajemen Laba, Pengungkapan Lingkungan Perusahaan dan Mekanisme Tata Kelola Perusahaan - Machmuddah, Zaky; Syafruddin, Muchamad; Muid, Dul; Utomo, St. Dwiarso (Jurnal Dinamika Akuntansi dan Bisnis, 2017)
The purpose of this study is to examine the effect of earnings management on corporate environmental disclosure with corporate governance mechanisms as a moderating variable. Population of this study is all companies listed in Indonesian Stock Exchange between 2008 and 2011. The samples size is 61 companies or 144 annual reports selected by using purposive sampling method. The data was analysed by employing multiple regression method. The result of this study demonstrated that earnings management significantly affected corporate environmental disclosure. Corporate governance mechanisms represented by proportion of independent board of directors and the number of audit committees moderated the effect of earnings management on corporate environmental disclosure. Meanwhile, the number of board of directors meetings and the number of audit committees meetings did not moderate the effect of earnings management on corporate environmental disclosure. The practical implication of this study is that the government needs to propuse a policy to reduce opportunistic action of managers in order to optimize shareholders and stakeholders decision making process